THE INFLUENCE OF CRITICAL FACTORS ON THE BEHAVIOR INTENTION TO COMPUTERIZED ACCOUNTING SYSTEMS (CAS) IN CEMENT MANUFACTURES IN LIBYA - Abdullah Naheb, Omran; Sukoharsono, Eko Ganis; Baridwan, Zaki (The International Journal of Accounting and Business Society, 2017)
Due to the rapid  change  in technology,  businesses  prefer  to track  monetary  transactions using computerized system and the advancements in information technology have eventually led to the introduction  of  Computerized  Accounting  Systems (CAS) to  help  produce  relevant,  trusted,  and representative  financial reports for both management and external users for decision-making without errors.  The shifting from conventional accounting system in Libyan organizations to Computerized Accounting Systems (CAS) resulted in some company’s staff’s resistance on the adoption of the new technologies. Therefore, this study aims to examine the Influence of Critical  Factors  on the Behavior Intention to Computerized Accounting Systems (CAS) In Cement Manufactures  In Libya which are, Performance    Expectancy,   Effort   Expectancy,   Facilitating  Conditions,   Self-efficacy  and   Task- technology fit (TTF) to accountant  Behavioral  Intentions  (ABI) of using (CAS) in Libyans cements organizations. This study utilized quantitative  research  method and survey questionnaires  distributed 240  forms to  employee  of in  accounting  and  finance  department  in  four  biggest  Libyan  cement manufacturers,  Al- Murgab,  Lubda,  Souk Al khamis  and  Zalitan.  The 189 returned forms were analyzed using PLS software.  The result  of analysis  hypothesis revealed  that  there  is a significant effect among  all  variables  to  Behavioral  Intentions,  but,  only,  Effort  Expectancy  does  not  have impacts   on   the   Behavior   Intention   to   Computerized   Accounting   Systems  (CAS)  In   Cement Manufactures In Libya.